Opioid-Sparring and Multimodal Analgesia as Parts of Enhanced Recovery After Surgery (ERAS) Applied In The Ksatria Airlangga Floating Hospital - Pratama Ananda; Bambang Pujo Semedi; Christrijogo Sumartono Waloejo; Arie Utariani (Faculty of Medicine-Universitas Airlangga, 2021)
Introduction: Enhanced Recovery After Surgery (ERAS) protocol is a perioperative multimodal service program designed to achieve a faster surgical recovery period and a better outcome, the key in reducing morbidity in surgery is by reducing the